The NARBO Performance Benchmarking Workshop to review performance indicators, Surabaya, Indonesia, 16-17 April 2009: A report submitted to DHV BV, Indonesia - Inocencio, Arlene B. (Animo Repository, 2009)
This report contains some specific and general observations and views in connection with the 16-17 April 2009 Workshop aimed to review the NARBO performance indicators. The workshop is part of the preparations for a planned benchmarking for 12 more river basin organizations (RBO) in 2009. The workshop had two parts: (1) review of the NARBO performance indicators and putting them into the Indonesian context before applying to more RBOs; and (2) planning for the 2009 RBO performance benchmarking. The first part was attended by all invited RBOs, guests from ADB funded projects, and benchmarking consultants while the second part was attended by the workshop organizers, benchmarking consultants and the NARBO-Indonesia (form PJT1) representative. This workshop was largely supported by the DGWR RBO Performance Monitoring Unit.